NETWORK DEVELOPMENT OF THE PUSHCHINO RADIO ASTRONOMY OBSERVATORY OF ASC LPI - Dumsky, D. V.; Isaev, E. A.; Pugachev, V. D.; Samodurov, V. A.; Likhachev, S. F.; Shatskaya, M. V.; Kitaeva, M. A. (Одеські астрономічні публікації, 2012)
All main changes in the network of the Pushchino Radio Astronomy Observatory has been related to introduction of the buffer data center in the recent years, upgrading internal and external communication channels and the exploitation of ip-telephony.